The immunoregulatory and allergy-associated cytokines in the aetiology of the otitis media with effusion - Marina G. Smirnova; John P. Birchall; Jeffrey P. Pearson (Mediators of Inflammation)
Inflammation in the middle ear mucosa, which can be provoked by different primary factors such as bacterial and viral infection, local allergic reactions and reflux, is the crucial event in the pathogenesis of otitis media with effusion (OME). Unresolved acute inflammatory responses or defective immunoregulation of middle inflammation can promote chronic inflammatory processes and stimulate the chronic condition of OME. Cytokines are the central molecular regulators of middle ear inflammation and can switch the acute phase of inflammation in the chronic stage and induce molecular-pathological processes leading to the histopathological changes accompanying OME. In this review we present cytokines identified in otitis media, immunoregulatory [interleukin (IL)-2, IL-10, transforming growth factor-β]) and allergy associated (IL-4, IL-5, granulocyte-macrophage colony-stimulating factor), as crucial molecular regulators, responsible for chronic inflammation in the middle ear and the chronic condition of OME.